Constructing global order : agency and change in world politics - Acharya, Amitav (Cambridge University Press, 2018)
"For a long time, international relations scholars have adopted a narrow view of what is global order, who are its makers and managers, and what means they employ to realize their goals. Amitav Acharya argues that the nature and scope of agency in the global order - who creates it and how - needs to be redefined and broadened. Order is built not by material power alone, but also by ideas and norms. While the West designed the post-war order, the non-Western countries were not passive. They contested and redefined Western ideas and norms, and contributed new ones of their own making. This book examines such acts of agency, especially the redefinitions of sovereignty and security, shaping contemporary world politics. With the decline of Western dominance, ideas and agency from the Rest may make it possible to imagine and build a truly global order"--